Math, asked by stefern19, 6 months ago

find dy/dx if xy = 3x^2-2y^2​

Answers

Answered by kulkarninishant346
2

First, let us find  

d

y

d

x

.

x

3

+

y

3

=

1

by differentiating with respect to  

x

,

3

x

2

+

3

y

2

d

y

d

x

=

0

by subtracting  

3

x

2

,

3

y

2

d

y

d

x

=

3

x

2

by dividing by  

3

y

2

,

d

y

d

x

=

x

2

y

2

Now, let us find  

d

2

y

d

x

2

.

by differentiating with respect to  

x

,

d

2

y

d

x

2

=

2

x

y

2

x

2

2

y

d

y

d

x

(

y

2

)

2

=

2

x

(

y

2

x

y

d

y

d

x

)

y

4

by plugging in  

d

y

d

x

=

x

2

y

2

,

d

2

y

d

x

2

=

2

x

[

y

2

x

y

(

x

2

y

2

)

]

y

4

=

2

x

(

y

2

+

x

3

y

)

y

4

by multiplying the numerator and the denominator by  

y

,

d

2

y

d

x

2

=

2

x

(

y

3

+

x

3

)

y

5

by plugging in  

y

3

+

x

3

=

1

,

d

2

y

d

x

2

=

2

x

y

5

Answered by mathdude500
4

Question :-

\bf \:If \: xy =  {3x}^{2} -  {2y}^{2} , \: find \: \dfrac{dy}{dx}

Answer

Given :-

\bf \:xy =  {3x}^{2} -  {2y}^{2}

To Find :-

\bf \:\dfrac{dy}{dx}

Formula used :-

\bf \:\dfrac{d}{dx} {x}^{n}  = n {x}^{n - 1}

\bf \:\dfrac{d}{dx}uv = u \dfrac{d}{dx}v + v\dfrac{d}{dx}u

Solution :-

\bf \:xy =  {3x}^{2} -  {2y}^{2}

Differentiate w. r. t. x, we get

\bf\implies \:\dfrac{d}{dx}xy =  \dfrac{d}{dx}({3x}^{2} -  {2y}^{2})

\bf\implies \:x\dfrac{d}{dx}y + y\dfrac{d}{dx}x = 3\dfrac{d}{dx} {x}^{2} - 2\dfrac{d}{dx} {y}^{2}

\bf\implies \:x\dfrac{dy}{dx}  + y = 6x - 4y\dfrac{dy}{dx}

\bf\implies \:(x + 4y)\dfrac{dy}{dx}   =  6x - y

\bf\implies \:\dfrac{dy}{dx}  =  \dfrac{6x - y}{x + 4y}

Similar questions